2015
DOI: 10.5604/12321966.1185784
|View full text |Cite
|
Sign up to set email alerts
|

Life quality of women with breast cancer after mastectomy or breast conserving therapy treated with adjuvant chemotherapy

Abstract: I. Life quality of women with breast cancer after mastectomy or breast conserving therapy treated with adjuvant chemotherapy. Ann Agric Environ Med. 2015; 22(4): 724-730. doi: 10.5604/12321966.1185784 Abstract Introduction. Breast cancer is the most frequent malignant neoplasm in women. The evaluation of the quality of life has become a treatment parameter as important as survival. Objective. The aim of the study was evaluation of the quality of life among women treated for breast cancer who underwent surg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 18 publications
3
17
1
3
Order By: Relevance
“…Moreover, the cancer‐related characteristics of the target patients in previous QoL studies varied (e.g., breast cancer stage, cancer duration, pre‐ or post‐menopause), which makes it difficult to compare the QoL results across studies. This highlights the importance of adjusting for patient's characteristics (e.g., breast cancer‐related characteristics, demographics) when evaluating the association between treatment and QoL, because patients' demographics (e.g., education; Chen, Liu, Wang, Liu, & Chen, ; Kaminska et al, ) and cancer‐related characteristics (e.g., cancer stage; Chen et al, ; Huang et al, ) may influence QoL. We found that the QoL of breast cancer patients varied with cancer stage and educational level (i.e., the results of simple linear regression analyses in Table ), although these trends were insignificant in subsequent adjusted analyses (i.e., the results of multiple linear regression analyses in Table ).…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Moreover, the cancer‐related characteristics of the target patients in previous QoL studies varied (e.g., breast cancer stage, cancer duration, pre‐ or post‐menopause), which makes it difficult to compare the QoL results across studies. This highlights the importance of adjusting for patient's characteristics (e.g., breast cancer‐related characteristics, demographics) when evaluating the association between treatment and QoL, because patients' demographics (e.g., education; Chen, Liu, Wang, Liu, & Chen, ; Kaminska et al, ) and cancer‐related characteristics (e.g., cancer stage; Chen et al, ; Huang et al, ) may influence QoL. We found that the QoL of breast cancer patients varied with cancer stage and educational level (i.e., the results of simple linear regression analyses in Table ), although these trends were insignificant in subsequent adjusted analyses (i.e., the results of multiple linear regression analyses in Table ).…”
Section: Discussionmentioning
confidence: 80%
“…The QoL of patients with breast cancer, worsened by the cancer it- Hwang et al, 2013;Tiezzi et al, 2017, radiotherapy only;Rahn et al, 1998;Xiao et al, 2016, mastectomy only;Kaminska et al, 2015;Szutowicz-Wydra et al, 2016), whereas this study comprehensively evaluated the QoL across different cancer treatments. We found that the use of chemotherapy had the most significant association with the QoL of breast cancer survivors, with adjustment for patient's characteristics and other breast cancer treatments; no significant association was not found for other types of breast cancer treatment.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Furthermore, compared with mastectomy, breast‐conserving surgery (BCS) causes less physical disfigurement and psychological trauma. The quality of life for patients after BCT continues to be debated . The differences in stigma and psychological condition between surgery modalities is controversial…”
Section: Introductionmentioning
confidence: 99%
“…The quality of life for patients after BCT continues to be debated. [17][18][19] The differences in stigma and psychological condition between surgery modalities is controversial. 20 Neoadjuvant chemotherapy (NACT) is defined as the application of systematic therapy prior to breast surgery.…”
Section: Introductionmentioning
confidence: 99%